An Integrated Approach to Obesity Management: Clinical Synergy Between GLP-1 Receptor Agonists and Sports Medicine. A Narrative Review. - Kociuba, Julia; Kruczek , Zuzanna; Kudła, Martyna; Krawczyk , Agata; Pawełczak, Natalia; Kołkowicz , Dorota; Czechowicz, Paweł; Czechowicz, Justyna; Antkiewicz, Mikołaj; Arczyńska, Aleksandra; Drozd, Maria; Łobaza, Paulina; et al. (Quality in Sport, 2026)
Background. Obesity is a complex neuroendocrine disease requiring long-term management. The emergence of GLP-1 receptor agonists has revolutionized weight loss outcomes; however, pharmacological monotherapy often leads to significant lean body mass (LBM) loss and metabolic adaptation. Aim. To analyze the clinical synergy between incretin-based pharmacotherapy and sports medicine protocols, focusing on functional tissue preservation and long-term metabolic health. Material and methods. A comprehensive review of scientific literature (2021–2026) was conducted, incorporating data from phase III clinical trials (STEP, SURMOUNT, SELECT) and exercise physiology research during pharmacological weight loss. Results. GLP-1 RA monotherapy results in LBM loss comprising 20–40% of total weight reduction. Structured resistance and aerobic training mitigates this loss, enhances muscle quality, and preserves bone mineral density. Combined therapy achieves superior visceral fat reduction and attenuates systemic inflammation while maintaining a higher basal metabolic rate compared to pharmacotherapy alone. Conclusions. Integrating sports medicine with modern pharmacotherapy represents a new standard in obesity treatment. Physical activity serves as a "metabolic anchor," preventing weight regain and improving patients' health-related quality of life (HRQoL).